PENGARUH KEKUATAN MINDSET POSITIF MAHASISWA UNTUK MENUNJANG TERCAPAINYA TUJUAN PENDIDIKAN - Jihan Nabilatus Sholihah; Anjar Dwi Setyorini; Firdha Yusmar; I Ketut Mahardika; Rizka Elan Fadilah (Pendidikan Fisika FKIP UNEJ, 2022)
Indonesia has educational goals that have been regulated in its law, but these goals are still not in line with what is happening in the field. There are still many students who only do education but do not know anything about the importance and nature of education itself. As a result, they do not find love and a sense of comfort with their education which can affect the realization of Indonesia's educational goals as the nation's successor. The research method in this article uses the literature method. Here in this article we will invite you to feel how beautiful education is with the power within yourself